Quasi-periodic spicule-like cool jets driven by Alfven pulses - Singh B.; Srivastava A.K.; Sharma K.; Mishra S.K.; Dwivedi B.N. (Oxford University Press, 2022)
We perform a 2.5D magnetohydrodynamic simulation to gain a comprehensive understanding of the formation of spicule-like cool jets caused by initial transverse velocity pulses akin to Alfven pulses in the solar chromosphere. We invoke multiple velocity (Vz) pulses between 1.5 and 2.0 Mm in the solar atmosphere, which create the initial transverse velocity perturbations. These pulses transfer energy non-linearly to the field-aligned perturbations via the ponderomotive force. This physical process further creates magnetoacoustic shocks followed by quasi-periodic plasma motions in the solar atmosphere. The field-aligned magnetoacoustic shocks move upwards, which subsequently causes the quasi-periodic rise and fall of chromospheric plasma into the overlying corona as thin and cool spicule-like jets. The magnitude of the initial applied transverse velocity pulses is taken in the range of 50-90 km s-1. These pulses are found to be strong enough to generate spicule-like jets. We analyse the evolution, kinematics and energetics of these spicule-like jets. We find that the transported mass flux and kinetic energy density are substantial in the local solar corona. These mass motions generate in situ quasi-periodic oscillations on the scale of 4.0 min above the transition region.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: MHD; shock waves; Sun; chromosphere; corona; oscillations; waves; Chromophores; Kinetic energy; Kinetics; Magnetoplasma; Shock waves; Magnetoacoustics; Magnetohydrodynamic simulations; Quasi-periodic; Shock-waves; Solar atmosphere; Chromosphere; Transverse velocity; Velocity pulse; Magnetohydrodynamics